2015
DOI: 10.5057/ijae.ijae-d-15-00010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smell in Space Perception

Abstract: Abstract:Waiting is an inevitable part of life and the spaces in which we wait can contribute to either improve or worsen the experience. This paper covers the process and results of "The waiting room", analyzing if the presence of specific smells has a significant impact in how the room and the waiting experience are perceived. Two different odorants were selected, lavender (relaxing) and orange (stimulating); 63 participants from 32 different countries were assigned into three groups (between-groups approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…It is conceivable that the process of mental imagery activated by olfactory stimulation could be of a different, albeit complementary, nature to that induced by the mental imagery instruction: olfactory stimulation induce more diverse and less product‐related images, and the mental imagery instruction refocus these ‘free associations’ around the product, thus enabling the respondent to produce more ideas. On the other hand, previous research has highlighted the power of scents to improve attention related to a task (Vilaplana & Yamanaka, 2015). The use of scents could thus improve people's concentration abilities, and improve the efficiency of the mental imagery instruction.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that the process of mental imagery activated by olfactory stimulation could be of a different, albeit complementary, nature to that induced by the mental imagery instruction: olfactory stimulation induce more diverse and less product‐related images, and the mental imagery instruction refocus these ‘free associations’ around the product, thus enabling the respondent to produce more ideas. On the other hand, previous research has highlighted the power of scents to improve attention related to a task (Vilaplana & Yamanaka, 2015). The use of scents could thus improve people's concentration abilities, and improve the efficiency of the mental imagery instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Research has in the meantime shown that auditory landmark information can be just as useful for spatial orientation as visual information (Hamburger & Röser, 2014; Karimpur & Hamburger, 2016). However, olfactory information is common in combination with spatial perception (e.g., Vilaplana & Yamanaka, 2015), but rarely combined with spatial orientation (e.g., Gottfried & Dolan, 2003). Therefore, the question remains whether humans use olfactory information as landmark-like information for spatial orientation in everyday life, and if so, how?…”
Section: Olfactory Cues For Navigationmentioning
confidence: 99%
“…Debido a la cultura occidental ocularcentrista, la modernidad y los mass media es común que el arquitecto diseñe enfatizando solo lo visible del espacio: la forma, la geometría (Dalton, 2012), lo material-tecnológico y los aspectos estéticos, rezagando los otros sentidos y el papel que pueden tener el olor, el sonido, la luz, la temperatura y el viento (Vilaplana & Yamanaka, 2015). Estos permiten una experiencia más completa (Costantini et al, 2011;Jelić, 2015;Jelić et al 2016), ya que lo 'invisible' acompaña lo visible, sea que provenga del entorno natural o del 'emitid0' por los elementos tectónicos del espacio arquitectónico.…”
Section: The Experience Of Architectural Space-time a Phenomenologica...unclassified